Pengaruh Total Asset Turnover Dan Current Ratio Terhadap Return On Equity Pada PT Vale Indonesia, Tbk Periode 2015-2024 - Rohmat Turyono; Arif Surahman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to determine the influence of total asset turnover and current ratio on return on equity at PT Vale Indonesia Tbk. , during the period 2015–2024, both individually and jointly. The ROE variable is one of the most important profitability indicators in the analysis of a company's financial performance. ROE measures a company's ability to generate net profit based on the total equity owned by shareholders. This study uses a quantitative associative research method with hypothesis testing. The study's population comprises the company's financial statements, with a sample of its balance sheet and income statement from 2015 to 2024. Secondary data in the form of the company's annual financial statements, obtained from its official website, were used for the analysis. Data analysis techniques include classical assumption tests, multiple linear regression tests, coefficient of determination tests, t-tests and F-tests. The results of the study indicate that total asset turnover has no partial effect on return on equity, with a calculated t-value of 1.448 (less than the t-table value of 2.36462) and a significance value of 0.198 (greater than 0.05). Therefore, H0 is rejected and Ha is accepted. The current ratio does not affect return on equity, with a calculated t-value of 1.710 (less than the t-table value of 2.36462) and a significance value of 0.138 (greater than 0.05). Concurrently, total asset turnover and current ratio do not have a significant effect on return on equity. The calculated F-value is smaller than the F-value (3.927 < 4.46) and the significance value is greater than the alpha value (α = 0.05), namely 0.081 > 0.05. Therefore, it can be concluded that H0 is rejected and Ha is accepted